Some new integral operators: sufficient conditions for their Univalence - Georgia Irina Oros; Gheorghe Oros; Alina Alb Lupas (Penerbit Universiti Kebangsaan Malaysia, 2011)
In this paper we define the integral operators with the forms:The operators generalise some integral operators studied by Owa, Pascu and Pescar. The original results contained in the paper give sufficient conditions for the univalence of those integral operators.